Ultrafast plasmonic lasing from a metal/semiconductor interface. Issue 31 (11th June 2020) - Wang, Jian; Jia, Xiaohao; Wang, Zhaotong; Liu, Weilong; Zhu, Xiaojun; Huang, Zhitao; Yu, Haichao; Yang, Qingxin; Sun, Ye; Wang, Zhijie; Qu, Shengchun; Lin, Jie; et al.
Abstract : Non-hybridized plasmonic nanowire lasers demonstrate ultrafast lasing dynamics and a comparable threshold to their hybrid counterparts. Abstract : To date, plasmonic nanowire lasers mostly adopt hybrid plasmonic waveguides, while there is a lack of study in terms of the confinement effect and the corresponding ultrafast dynamics of non-hybridized plasmonic lasers. Here, we report ultrafast plasmonic nanowire lasers composed of a single CH3 NH3 PbBr3 nanowire on a silver film without any insulating layer at room temperature. The non-hybridized plasmonic nanowire lasers exhibit ultrafast lasing dynamics with around 1.9 ps decay rate and 1 ps peak response time. Such values are among the best ones ever reported. Interestingly, the threshold of the non-hybridized plasmonic nanowire lasers is in the same order as that of their hybrid counterparts. The low threshold is due to the ultra-flat single-crystal silver films and high-quality single-crystal perovskite nanowires. The non-hybridized plasmonic lasing in CH3 NH3 PbBr3 nanowires originates from the stimulated emission of an electron–hole plasma based on our experiments. This work deepens the understanding of non-hybridized plasmonic lasers and paves the way to design electric pump plasmonic lasers by getting rid of insulating layers.